Itu Analisis Kesiapan Organisasi dan Implementasi Sistem Informasi Manajemen Proyek pada Perusahaan - Hadi Winarto; Franciskus Antonius Alijoyo (OIKOS: Jurnal Kajian Pendidikan Ekonomi dan Ilmu Ekonomi, 2025)
The implementation of a project management information system (SIMP) can bring improvements in efficiency, effectiveness, and transparency in managing projects, contributing to the achievement of the company's business goals. However, before implementing SIMP, companies need to analyze their organizational readiness so that the implementation can run smoothly and provide maximum benefits. This research aims to analyze the level of organizational readiness and SIMP implementation in the company. The research method used is qualitative method. Data collection is done through literature studies, then the collected data is analyzed through three stages, namely data reduction, data presentation, and conclusion drawing. The results show that organizations must pay attention to several factors of organizational readiness in implementing SIMP which include support from the management level, a supportive organizational culture, a clear organizational structure, the availability of adequate technological infrastructure, and the existence of human resource expertise. After the organization ensures that these factors have been met, only then can the SIMP implementation process be carried out with the stages of planning, implementation, and operation.